Four years on: A longitudinal study assessing the impact of membership of a virtual community of practice - Allan, Barbara; Hunter, Bob; Lewis, Dina (Proceedings of the International Conference on Networked Learning, 2006)
This paper explores the long term impact of a virtual learning community (VLC) from the perspective of community members and their employing organization. It argues that membership potentially has a significant impact on individual identities and careers, and that managed communities provide an important means for strategic workforce development. The study evaluates the impact of membership of a VLC over a four year period within the context of the theoretical frameworks of communities of practice and identity theory. The concept of boundary crossing is also explored in relation to VLCs. The paper considers the benefits to host organisations in supporting structured VLCs as a means of enabling workforce development and supporting change and innovation.